(untitled) (Journal of Hama University, 2025)
The research aimed to study the personal and social characteristics that influence agricultural extension workers’ support for using smart phones in their extension activity. To achieve the research objectives, a questionnaire form was designed and information was collected from members of the studied sample using a personal interview on a random sample of 100 agricultural extension workers in various regions. Latakia Governorate. The results showed that most agricultural extension workers own 99% mobile phones (89% of which are modern phones), and there is a high desire among extension workers to use smart phones in their extension work. The results also indicated that there were statistically significant differences (sig<0.05) in support for extension workers’ use of smartphones in agricultural extension according to the variable of age, number of years of service, availability of internet service, and according to the guide’s ability to use technology, and there were no statistically significant differences (sig>0.05). In supporting extension workers’ use of smartphones in agricultural extension according to the educational level of the extension agent, the research recommended providing electronic extension applications, and the need to encourage their use by farmers and extension workers alike, and motivate farmers to adopt them, in addition to conducting training courses in the field of developing and using computer software in Indicative units, and the necessity of adopting the indicative electronic approach to reduce cost and save time and effort.